Description of a new species of Ixodes (Acari: Ixodidae) and first report of Ixodes lasallei and Ixodes bocatorensis in Brazil - Onofrio, Valeria C.; Guglielmone, Alberto A.; Barros-Battesti, Darci M. [UNESP]; Gianizella, Sergio L.; Marcili, Arlei; Quadros, Rosiléia M.; Marques, Sandro; Labruna, Marcelo B. (Elsevier, 2020)
In a recent study, we relegated the taxon Ixodes aragaoi Fonseca, 1935 to a junior synonym of Ixodes fuscipes Koch, 1844, and reinstated Ixodes spinosus Neumann, 1899 (a former synonym of I. fuscipes) to a valid species. We examined all lots of ticks formerly identified as I. fuscipes or I. aragaoi in three tick collections of Brazil. Through morphological analysis, some of the examined specimens could not be assigned to either I. fuscipes or I. spinosus based on the examination of the type specimens of these two species. Herein, we report these ticks to represent three different species: Ixodes catarinensis n. sp. Onofrio & Labruna, Ixodes lasallei Méndez Arocha and Ortiz, 1958, and Ixodes bocatorensis Apanaskevich and Bermúdez, 2017. The latter two species are reported for the first time in Brazil. Phylogenetic analysis inferred from the tick 16S rRNA gene partial sequences corroborated our morphological analysis, indicating that I. spinosus, I. lasallei, I. bocatorensis, and I. catarinensis n. sp. form a natural group of neotropical ticks. With the present study, the number of Ixodes species in Brazil increases from 9 to 12. We propose a new identification key for females and males of Ixodes species currently recognized in Brazil.
Keywords: Ixodids; South America; Taxonomy; Ticks